Effects of mini trampoline exercise on male gymnasts` physiological parameters: a pilot study - Karakollukçu, M.; Aslan, C. S.; Paoli, A.; Bianco, A.; Sahin, F. N. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: There are limited studies that indicate the effects of trampoline exercise on strength and other physiological parameters. This study aims to determine whether twelve weeks of trampoline exercise would have any effects on the physical and physiological parameters of male gymnasts.